Surgery : PreTest Self-Assessment and Review - Kao, Lillian S. and Lee, Tammy (London Mc Graw Hill)
"The closest you can get to seeing the USMLE Step 2 CK without actually taking it. Surgery: PreTest Self-Assessment & Review is the perfect way to assess your knowledge of surgery for the USMLE Step 2 CK and shelf exams. You'll find 500 USMLE-style questions and answers that address the clerkship's core competencies along with detailed explanations of both correct and incorrect answers. All questions have been reviewed by students who recently passed the boards and completed their clerkship to ensure they match the style and difficulty level of the exam. 500 USMLE-style questions and answers. Detailed explanations for right and wrong answers. Targets what you really need to know for exam success. Student tested and reviewed"--Provided by publisher.
Include Index and Illustration
Keywords: Surgery